ILLOCUTIONARY ACTS AND THEIR RELATIONSHIPS WITH INTERVIEWEES LEVEL OF TRUSTWORTHINESS IN GIVING INFORMATION DURING THE MAKING OF INVESTIGATION REPORTS: A CASE STUDY IN SITUBONDO POLICE STATION - Ahmad Firdaus; Firqo Amalia; Sufil Lailiyah (Sanata Dharma University, 2019)
This research analyzes the level of interviewees trustworthiness in giving information during the making of investigation reports in Situbondo Police Station. Searles theory of speech acts is used to analyze the data. The level of the interviewees trustworthiness is based on the information given by the police officers, which is integrated with the result of the illocutionary act analysis. This qualitative descriptive research produces deep descriptions of the utterances stated by interviewees. Taxonomic analysis proposed by Spreadly is used to classify the data based on the types of illocutionary acts found. Componential analysis is used to reveal the interrelationship between variables. The result of this research reveals that there is a strong relationship between an interviewees trustworthiness and kinds of illocutionary acts, and that assertive, which produces a large number of less trustworthy utterances, is the most frequently found illocutionary act.